Effects of three‐month streptozotocin‐induced diabetes in mice on blood platelet reactivity, COX‐1 expression and adhesion potential. Issue 1 (27th February 2019) - Przygodzki, Tomasz; Kassassir, Hassan; Talar, Marcin; Siewiera, Karolina; Watala, Cezary
Summary: Diabetes is associated with an increased risk of cardiovascular disease. This is partially attributed to an altered activation status of blood platelets in this disease. Previously, alterations have been shown in COX‐1 and protease activated receptor (PAR)‐3 receptor expression in platelets in two animal models of diabetes, there have not been studies which address expression of these proteins in mice with long‐term streptozotocin (STZ)‐induced diabetes. We have also addressed the effect of diabetes on platelet adhesion under flow conditions. With the use of flow cytometry, we have shown that certain markers of platelet basal activation, such as active form of αII b β3 and of CD40L were increased in STZ‐induced diabetic mice. Platelets from STZ‐induced diabetic mice were also more reactive when stimulated with PAR‐4 activating peptide as revealed by higher expression of active form of αII b β3, membrane‐bound on vWillebrand Factor and binding of exogenous fluorescein isothyanate‐labelled fibrinogen. Expression of COX‐1 and production of thromboxane A2 in platelets of STZ‐induced diabetic mice were higher than in control animals. We observed no effect of diabetes on ability of platelets to form stable adhesions with fibrinogen in flow conditions. We conclude that although certain similarities exist between patterns of activation of platelets in animal models of diabetes, the differences should also be taken into account.